Why Globalization Works - Wolf, Martin, 1946- (New Haven ; London : Yale University Press, 2004)
"The debate on globalization has reached a level of passionate intensity that inhibits rational discussion. In this book, one of the world's foremost economic commentators explains how globalization works and why it makes sense. Martin Wolf confronts the charges against globalization, delivers a devastating critique of each and outlines a more hopeful future."--BOOK JACKET.
Bibliographical notes (p. [364]-380) and Index (p. [381]-398)
Keywords: Globalization -- Economic aspects; International economic relations